2023
DOI: 10.33003/fjs-2022-0606-1179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Market Patronage on the Traffic Situation in Benin Metropolis, Nigeria

Abstract: This paper examines the influence of market patronage on the traffic situation in Benin City, Nigeria. Nine market routes were studied, and a well-structured questionnaire administered randomly and systematically was used to collect data from 407 respondents. Descriptive and correlation techniques were used to analyse the responses. Most of the markets were found to be situated along transit routes, and operated every day, resulting in street trading and parking which contributed 76.2 percent to the traffic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In urban evacuation, network connectivity is an important planning indices that affects the evacuation efficiency of motor vehicles. Low road connectivity will cause traffic congestion [58,59]. This study found that the influence of network connectivity on CRD pedestrian evacuation efficiency was not significant using ODOE significance analysis.…”
Section: Parametric and Synergistic Effect Analysismentioning
confidence: 74%
“…In urban evacuation, network connectivity is an important planning indices that affects the evacuation efficiency of motor vehicles. Low road connectivity will cause traffic congestion [58,59]. This study found that the influence of network connectivity on CRD pedestrian evacuation efficiency was not significant using ODOE significance analysis.…”
Section: Parametric and Synergistic Effect Analysismentioning
confidence: 74%
“…The use of land determines the types of activities that can be accommodated in an area. According to a study conducted by Ayo-Odifiri, Fasakin and Okoko (2018), the factors that influence the quality and viability of an area's attractions and activities are the transport system's efficiency and accessibility. This suggests that the failure of one sector of the transportation system could affect other sectors (Ayo-Odifiri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted by Ayo-Odifiri, Fasakin and Okoko (2018), the factors that influence the quality and viability of an area's attractions and activities are the transport system's efficiency and accessibility. This suggests that the failure of one sector of the transportation system could affect other sectors (Ayo-Odifiri et al, 2018). The relationship between the use of land and traffic has been compared to that of an egg and chicken.…”
Section: Introductionmentioning
confidence: 99%
“…It could be an educational institution, a bank, an ATM, a hotel, a restaurant, a police station, etc. The people in the city use the road network to reach their utilities (Ayo-Odifiri et al 2017).…”
Section: Introductionmentioning
confidence: 99%